Observation on antioxidant activity from leaves, callus and suspension culture of Justicia gendarusa - Amid, Azura; Johan, Nurul Najwa; Jamal, Parveen; Wan Mohd Zain, Wan Norzaidani (2011)
This Antioxidant activity and phenolic compound was found in Justicia gendarussa (JG) via total phenolic content (TPC) and α,α-diphenyl-β-pycrilhydrazil hydrate (DPPH) radical scavenging assays. The assays were applied on aqueous and methanolic extracts of leaves, callus culture and cell suspension culture of JG. Callus was induced from green and matured leaves of JG cultured on Murashige and Skoog (MS) basal medium supplemented with different concentrations of 2,4- dichlorophenoxyacetic acid (2,4-D)or1-Naphthaleneacetic acid (NAA) and benzylaminopurine (BAP). Callus induced on NAA (1-Naphthaleneacetic acid) showed higher phenolic content and antioxidant activity compared to the one induced on 2,4-D. Highest total phenolic content; 88mg GAE/g was observed from callus culture induced with NAA and BAP while highest antioxidant activity (lowest IC50; 8.46x10-3mg/mL) was observed in the cell suspension